Supplement Treatment with NAC and Omega-3 Polyunsaturated Fatty Acids during Pregnancy Partially Prevents Schizophrenia-Related Outcomes in the Poly I:C Rat Model - Henriette Edemann-Callesen; Nadine Bernhardt; Elizabeth Barroeta Hlusicka; Franziska Hintz; Bettina Habelt; Rebecca Winter; Isabell Neubert; Meike Pelz; Alexandra Filla; Maria Luisa Soto-Montenegro; Christine Winter; Ravit Hadar (MDPI AG, 2023)
Background: Heightened levels of inflammation and oxidative stress are thought to be involved in the pathophysiology of schizophrenia. We aimed to assess whether intake of anti-inflammatory and anti-oxidant drugs during pregnancy prevents later schizophrenia-related outcomes in a neurodevelopmental rat model of this disorder. Methods: Pregnant Wistar rats were injected with polyriboinosinic-polyribocytidilic acid (Poly I:C) or saline and subsequently treated with either N-acetyl cysteine (NAC) or omega-3 polyunsaturated fatty acids (PUFAs) until delivery. Controls rats received no treatment. In the offspring, neuroinflammation and anti-oxidant enzyme activity were assessed on postnatal day (PND) 21, 33, 48, and 90. Behavioral testing was performed at PND 90, followed by post-mortem neurochemical assessment and ex vivo MRI. Results: The supplement treatment led to a quicker restoration of the wellbeing of dams. In the adolescent Poly I:C offspring, the supplement treatment prevented an increase in microglial activity and partially prevented a deregulation in the anti-oxidant defense system. In the adult Poly I:C offspring, supplement treatment partially prevented dopamine deficits, which was paralleled by some changes in behavior. Exposure to omega-3 PUFAs prevented the enlargement of lateral ventricles. Conclusion: Intake of over-the-counter supplements may assist in especially targeting the inflammatory response related to schizophrenia pathophysiology, aiding in diminishing later disease severity in the offspring.